BUMDes as an Alternative Resolution to the Conflict of Marine Tourism Management in Madura - Ikhwan, Mufarrijul; Safi, Safi; Yulianti, Rina (Universitas Airlangga, 2021)
The utilisation of coastal space for marine tourist destinations has developed rapidly, potentially resulting in conflict. Marine tourism managed by villagers in Bangkalan Regency exemplifies potential conflict in its implementation. In Labuhan Village, Sepulu Sub District, Bangkalan Regency mangrove tourism has resulted in a conflict of management between the communities in a village. It is well established that public participation is one variable that can affect the supportability of the coastal environment for marine tourism development; however, non-participative management will also affect the sustainability of the tourism business. This research aims to formulate a model of marine tourism management policy through village owned enterprises (BUMDes). Such a policy model is expected to minimise the conflict of spatial management. To achieve this objective, socio-legal research was used with factual and conceptual approaches. The results show that the marine tourism management policy in Madura coastal area is managed more by the mangrove farmer group, tourism consciousness group (pokdarwis) and community supervisor group (pokwasmas). Very few have been managed by BUMDes. BUMDes is a legitimised institution for managing marine tourism in coastal areas because BUMDes can stimulate and activate the rural economic wheel managed by villagers. Juridical construction of marine tourism management through BUMDes can be legitimised based on the Village Act. Village Regulation and legal entity organisation are legal figures underlying marine tourism management through BUMDes as governed by the Village Act and Minister of Village, Transmigration, and Disadvantaged Region's regulation of the establishment, administration, management and dismissal of BUMDes.